Kinetic Study on Ultrasound Assisted Biodiesel Production from Waste Cooking Oil - Widayat, Widayat; Hadiyanto, H; Sasongko, Setia Budi (ITB Journal Publisher, LPPM ITB, 2015)
The objective of this research was to studyÂ a kinetic model of biodiesel production from waste cooking oil assisted by ultrasound power. The model considered the biodiesel production process as a 2nd order reversible reaction, while its kinetic parameters were estimated using MATLAB, based on data extracted from Hingu, et al. [1]. The data represented experiments under low-frequency ultrasonic wave (20 kHz) and variations of temperature, power, catalyst concentration, and alcohol-oil molar ratio. Statistical analysis showed that the proposed model fits well to the experimental data with a determination coefficient (R2) higher than 0.9.